The influence of leaders past environmental-related experiences and positive deviance behaviour in green management practices [Pengaruh pengalaman berkenaan alam sekitar ketua syarikat dan perlakuan penyimpangan positif dalam amalan pengurusan hijau syarikat] - Jaaffar A.H.; Amran A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
There is limited research based on the perspective of neo-institutional that examines the cognitive pressures related to green management practices. The current study examined the relationship between the past environmental related experiences which one of the cognitive dimensions of leader in public listed company and its relationship with positive deviance behaviour in green management practices. The results revealed a significant positive relationship between the past environmental related experiences of the board of directors and positive deviance behaviour in green management practices; however for CEOs past environmental related experiences and its interaction effect with board of directors past environmental experiences are otherwise. This study reveals that the understanding regarding the intersection between sound corporate governance and green management practices is very important in companies deviating positively in green management practices. 2017 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.